Honey Robbing: Causes, Impacts and Preventive Measures - Xinyu Wang; Ting Huang; Quanzhi Ji; Jun Guo; Yazhou Zhao (Insects)
Honey robbing, which typically occurs during times of food scarcity, is a perilous foraging strategy for bee colonies and presents a formidable challenge in the realm of beekeeping. This article provides a comprehensive and multifaceted exploration of honey robbing, including the morphology, behavioral traits, timing, and scope of this phenomenon. This exploration elucidates the specific manifestations of honey robbing, offering readers a deeper understanding of its various facets. Next, this article investigates the root causes of honey robbing by examining both abiotic and biotic factors. The resulting harms are outlined, and corresponding preventive and control measures are suggested. Finally, the article succinctly summarizes the current obstacles in research related to honey robbing and outlines promising avenues for future exploration. The objective of this study was to elucidate the occurrence mechanism of honey robbing, ultimately aiming to contribute to the sustainable growth of the beekeeping industry.